Rekonstruksi buku ajar berbasis kurikulum merdeka: Pengembangan E-Book Bahasa Inggris Berbasis Nilai Budaya untuk Fase E - Nur, Luluk Choirun Nisak (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2024)
This research aims to develop a Culture-based English e-book aligned with the Merdeka Curriculum for Phase E in MA Al-Bairuny, Jombang. The Merdeka Curriculum is expected to provide a more contextual and culturally relevant learning experience for students. Using the ADDIE method (Analysis, Design, Development, Implementation, Evaluation), this study focuses on the validation of the e-book product.The analysis phase identified the needs of students and teachers, highlighting that the current curriculum does not adequately address the cultural diversity of the students. The design phase resulted in an e-book with English content focusing on text types rooted in Indonesian culture. Material and media validation were conducted by education and media experts, resulting in